(untitled) (FUDMA Journal of Agriculture and Agricultural Technology, 2022)
This study examined the variability of five relevant rainfall characteristics: annual rainfall total, number of rainy days, length of the growing season, onset dates and cessation dates of rainfall, and their implications on Yam production in Makurdi and Gboko Benue State, Nigeria. Daily rainfall data from 1980 to 2015 was obtained from the Nigeria Meteorological Agency (NiMet), Makurdi, and Agro-Meteorological Station Yandev, Gboko, while yam production data from 1986 to 2011 was obtained from Benue State Agricultural and Rural Development Authority (BNARDA), Makurdi. The data were analyzed using trend, correlation, and regression analyses. In both Gboko and Makurdi, the results showed a variation and fluctuating tendency in rainfall characteristics of different degrees over time and space with the anomaly tilted toward a negative pattern. On the other hand, the results of the correlation and regression analyses between rainfall characteristics and yam production revealed insignificant positive and negative associations under the period under consideration except for Gboko where rainfall and rainy days were significant. We highlight the necessity for farmers in the study areas to plant early-maturing yam seedlings and pay attention to other factors of agricultural production in order to address the variability in rainfall characteristics especially the length of growing seasons (LGS).